Host–parasite interaction: an insight into the growth and physiological responses of sandalwood and associated host species - Verma, Kamlesh; Kumar, Ashwani; Kumar, Raj; Bhardwaj, Ajay Kumar; Devi, Sunita; Sharma, Aarju; Sharma, Prashant (Frontiers in Forests and Global Change, 2024)
Sandalwood (Santalum album L.) is categorized as vulnerable in IUCN Red list, and is also an industrially important tree species valued for its heartwood and aromatic oil. Sandalwood is a semiroot parasite tree which relies on its host plants for its water and nutrient requirements. Therefore, present investigation was conducted to understand growth and physiological interaction between parasite sandalwood grown with ten different host tree species. Results revealed that sandalwood grown with hosts Dalbergia sissoo and Casuarina equisetifolia showed higher growth performance, while among hosts, Syzygium cumini, followed by Citrus aurantium and Leucaena leucocephala performed better growth and physio-biochemical traits. The step-wise regression analysis and trait modeling indicated that six traits, namely, plant height, photosynthetic rate, relative water content, water potential, intercellular CO2 concentration, and total soluble protein contributed greater growth in the sandalwood, while four traits, namely, water potential, osmotic potential, leaf area, and total soluble protein contributed greater growth in the host species. The traits modeling study predicted greater growth of sandalwood with the hosts D. sissoo and C. equisetifolia, whereas among host species, prediction revealed greater growth of S. cumini and C. aurantium. Results concluded that host-parasite interaction modulated growth and physiological processes in the both sandalwood and hosts, and sandalwood plantations can be successfully grown with host species D. sissoo and C. equisetifolia.